Pengaruh Kepemilikan Institusional dan Koneksi Politik terhadap Penghindaran Pajak: Peran Moderasi Ukuran Perusahaan - Anggita Ayundasari; Dwi Septiani (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Sumatera Utara, 2026)
This study aims to examine the influence of institutional ownership and political connections on tax avoidance, with firm size as a moderating variable. A quantitative approach was employed using secondary data obtained from the annual financial reports of energy sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The sampling method used was purposive sampling, resulting in a final sample of six companies. Data analysis was conducted using panel data regression and moderated regression analysis (MRA) with the assistance of EViews 12 software. The results show that, simultaneously, institutional ownership and political connections have a significant effect on tax avoidance. Partially, institutional ownership has a positive effect on tax avoidance, while political connections show no significant effect. Furthermore, firm size is found to moderate the relationship between institutional ownership and tax avoidance, but does not moderate the relationship between political connections and tax avoidance.